Legal Analysis of Digital Zakat Management: Security, Literacy, and Regulatory Challenges - Mushdalifah, Mushdalifah; Subli, Mohamad; Susanti, Ririn; Zulkarnain, Zulkarnain (Constitutional Law Review, 2024)
Digital transformation in zakat management faces significant challenges regarding efficiency, transparency, and regulatory compliance. This study aims to explore the role of digital technologies in enhancing zakat collection and distribution by Amil Zakat Institutions (LAZ) in Indonesia. Using a qualitative literature review approach, this research analyzes key regulations, including the Electronic Information and Transactions Law (ITE Law), Data Protection Law, and relevant sharia fatwas on e-wallet usage. Findings indicate that digital technologies, such as web applications, e-wallets, and QRIS systems, enhance the flexibility and reach of zakat payments, thereby expanding the collection area to remote regions. Digitalization also facilitates automation of payments and enables transparency through real-time tracking of zakat funds. However, key challenges include data privacy, low digital literacy, and sharia compliance.The implications suggest that zakat institutions need to strengthen data security and promote digital literacy to address adoption barriers. Collaboration between the government, zakat institutions, and stakeholders is essential to ensure a trustworthy and efficient digital zakat system. This study recommends stronger regulations and continuous innovation to make zakat a sustainable economic empowerment tool.